Hygromechanical strains during the drying of Eucalyptus nitens boards - N. Pérez-Peña; A. Cloutier; F. Segovia; C. Salinas-Lira; V. Sepúlveda-Villarroel; L. Salvo-Sepúlveda; D.M. Elustondo; R. A. Ananías (Maderas: Ciencia y Tecnología, 2016)
Collapse and drying stresses are currently induced during the drying of Eucalyptus nitens in solid wood products. The purpose of this study was to investigate these drying stresses by measuring hygromechanical strains during the drying of Eucalyptus nitens boards.